2019
DOI: 10.3390/su11030799
|View full text |Cite
|
Sign up to set email alerts
|

Filmmaking and Crowdfunding: A Right Match?

Abstract: Broadly defined, culture is deemed the fourth pillar of sustainable development and increasing attention is currently being paid to how it can access all potential financial resources. In Europe, film production benefits from public financial support; however, film projects require large amounts of money to be completed and this support may prove insufficient in comparison with the actual need. This raises the question of identifying alternative financial resources that filmmakers could benefit from. Crowdfund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Supporting these measures, Gerber, Hui, and Kuo (2012) found the motivations of founders of FC included the seeking of rewards, supporting the creators, and social networking (Belleflamme et al, 2015;Chen & Wang, 2018;Daly, 2018;Hobbs et al, 2016;Mollick, 2014;Tekeo glu, 2015). Fanea-Ivanovici (2019) found the rewards offered by the FC projects included film-related experience or byproducts (e.g., mugs, T-shirts, posters, badges, DVDs, and invitations to the premiere), public acknowledgment, and the roles, ideas, opinions, suggestions from the film.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Supporting these measures, Gerber, Hui, and Kuo (2012) found the motivations of founders of FC included the seeking of rewards, supporting the creators, and social networking (Belleflamme et al, 2015;Chen & Wang, 2018;Daly, 2018;Hobbs et al, 2016;Mollick, 2014;Tekeo glu, 2015). Fanea-Ivanovici (2019) found the rewards offered by the FC projects included film-related experience or byproducts (e.g., mugs, T-shirts, posters, badges, DVDs, and invitations to the premiere), public acknowledgment, and the roles, ideas, opinions, suggestions from the film.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…In terms of research about the film industry, previous studies have frequently found the promotion of the film industry could help the growth of GDP, value-adding of related industries, employment, cultural consumption, citizen's awareness and social and cultural inclusion (Fanea-Ivanovici, 2019;Tera Consultants, 2014). FC has proven to be one of the most popular financing methods in film industry, and it brings longtail welfare of films as the funders are from all over the world and this may help to diversify the consumers in terms of gender, ethnicity, political opinions and so on (Booth, 2015;Herbert, 2018;Hobbs et al, 2016;Koçer, 2015;Loriguillo-L opez, 2017;Papadimitriou, 2017;Sørensen, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of crowdfunding has increased especially after the 2008 financial crisis. Many have turned to crowdfunding as a solution to the difficulty to raise fund (Bruton, Khavul, Siegel, & Wright, 2015;Fanea-Ivanovici, 2019). Although start-ups play important role in creating jobs and increasing economic growth, they frequently face difficulty to obtain financing due to several reasons such as lack of collateral, credit history, reputation and connections (Bade, 2018;Beck, Demirgüç-Kunt, & Peria, 2007).…”
Section: Overview Of Crowdfundingmentioning
confidence: 99%
“…The application of crowdfunding is expanding for various reasons and activities. It is used in various industries such as video game production (Smith, 2015), sports (Huth, 2018) and filmmaking (Fanea-Ivanovici, 2019). Technology and creative cultural projects are among popular projects that receive support from the crowd.…”
Section: Overview Of Crowdfundingmentioning
confidence: 99%